2019
DOI: 10.1080/03949370.2018.1561523
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Pied crows Corvus albus and breeding White-backed vultures Gyps africanus

Abstract: Evans KL. 2003. The potential for interactions between predation and habitat change to cause population 248 declines of farmland birds. Ibis. 146:1-13.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Within the Kimberley area, the only extant ground‐dwelling predators of vulture eggs and/or chicks are Chacma Baboon Papio ursinus or Vervet Monkey Chlorocebus pygerythrus . However, we could not find any published records of these species predating vulture chicks in the area, and in one published account of a monkey chasing a vulture from a nest, the monkey seemed unable (or did not attempt) to predate the egg, because the egg hatched a few weeks later (Johnson & Murn, 2019). Furthermore, it seems unlikely that the trees around Kimberley, which rarely exceed 15 m in height, would pose a real obstacle to a persistent Chacma Baboon or Vervet Monkey.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Within the Kimberley area, the only extant ground‐dwelling predators of vulture eggs and/or chicks are Chacma Baboon Papio ursinus or Vervet Monkey Chlorocebus pygerythrus . However, we could not find any published records of these species predating vulture chicks in the area, and in one published account of a monkey chasing a vulture from a nest, the monkey seemed unable (or did not attempt) to predate the egg, because the egg hatched a few weeks later (Johnson & Murn, 2019). Furthermore, it seems unlikely that the trees around Kimberley, which rarely exceed 15 m in height, would pose a real obstacle to a persistent Chacma Baboon or Vervet Monkey.…”
Section: Discussionmentioning
confidence: 80%
“…Another explanation for the low fledgling rate in our study year is nest abandonment, disturbance or other environmental factors. Previous work in the Kimberley area has shown that pied crows can negatively affect nesting white‐backed vultures (Johnson & Murn, 2019). We found no evidence of crow densities affecting breeding productivity, but the mechanism behind the impacts of pied crows on white‐backed vultures remains unclear and our data on crow density lacked a temporal component (i.e., throughout the egg incubation period) to assess this further.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerns about the growing pied crow Corvus albus population in southern Africa over the last 30 years (Cunningham et al, 2016) stem from the potential impacts on other species. For example, reports have suggested pied crows are a key predator of the IUCN endangered geometric tortoise Psammobates geometricus (Fincham & Lambrechts, 2014), as well as being nest predators and/or scavengers of bird species (Sensory Ecology, 2013), including critically endangered African white-backed vultures Gyps africanus (Johnson & Murn, 2019). Pied crows are also a cause of concern to some domestic livestock farmers (Pisanie, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Concerns about the growing pied crow Corvus albus population in southern Africa over the last 30 years (Cunningham et al, 2016) stem from the potential impacts on other species. For example, reports have suggested pied crows are a key predator of the IUCN endangered geometric tortoise Psammobates geometricus (Fincham and Lambrechts, 2014), as well as being nest predators/scavengers of bird species (Sensory Ecology, 2013), including critically endangered African white-backed vultures Gyps africanus (Johnson and Murn, 2019). Pied crows are also a cause of concern to some domestic livestock farmers (Pisanie, 2016).…”
Section: Introductionmentioning
confidence: 99%